1974
DOI: 10.1021/ja00810a010
|View full text |Cite
|
Sign up to set email alerts
|

Medium effects and quantum yields in the photoaddition of naphthalene and acrylonitrile. Chemical evidence on an exciplex structure

Abstract: The photoaddition of naphthalene and acrylonitrile at 313 nm and in hydroxy lie solvents to afford e«ífo-7-cyano-2,3-benzobicyclo[4.2.0]octa-2,4-diene (1), the mfo-8-isomer, and 1-and 2-naphthylpropionitrile (3 and 4) is investigated. The reactive state is naphthalene Si which is determined by kinetically relating quantum yields and fluorescence quenching dependences on acrylonitrile concentration. The fluorescence quenching is proposed to occur by charge-transfer exciplex formation. Good Stern-Volmer plots ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…Torbional Angles, deg C(l)C(7)C(8)C(9) 4.8 (3) C(l)C(2)0(3)C(4) C(7)C(8)C(9)C( 10) -6.2 (3) C(2)0(3)C(4)C(5) C(8)C(9)C(lO)C(ll) 2.5 (2) 0(3)C(4)C(5)C(1) C(lO)C(ll)C(l)C(7) -3.9 (2) C(5)C(l)C(2)0(3) C(9)C(lO)C(ll)C(l) 2.9 ( 2 ) C(4)C(5)C(l)C(2) C(ll)C(l)C(7)C (8) 0.0 (2) C( l)C(5)C(6)CU) C( 5)C(6)C( 7)C( 1 ) C(6)C(7)C(l)C(5) C(7)C( 1)45)C (6) 41.1 (2) -41.1 ( 2 ) 23.7 (2) 1.0 (2) -25.2 (2) -0.9 (2) -0.9 (2) 0.9 (2) 0.9 (2)…”
Section: Discussionunclassified
“…Torbional Angles, deg C(l)C(7)C(8)C(9) 4.8 (3) C(l)C(2)0(3)C(4) C(7)C(8)C(9)C( 10) -6.2 (3) C(2)0(3)C(4)C(5) C(8)C(9)C(lO)C(ll) 2.5 (2) 0(3)C(4)C(5)C(1) C(lO)C(ll)C(l)C(7) -3.9 (2) C(5)C(l)C(2)0(3) C(9)C(lO)C(ll)C(l) 2.9 ( 2 ) C(4)C(5)C(l)C(2) C(ll)C(l)C(7)C (8) 0.0 (2) C( l)C(5)C(6)CU) C( 5)C(6)C( 7)C( 1 ) C(6)C(7)C(l)C(5) C(7)C( 1)45)C (6) 41.1 (2) -41.1 ( 2 ) 23.7 (2) 1.0 (2) -25.2 (2) -0.9 (2) -0.9 (2) 0.9 (2) 0.9 (2)…”
Section: Discussionunclassified
“…This is to be compared with the case of the cycloaddition reaction of acrylonitrile with a-and Pnaphthols and their trimethylsilyl ethers. In these cases, the regioselectivity is governed by the position of the oxygen substituent (8). In our cases, the position of the naphthalene substituent does not affect the regioselectivity.…”
Section: Discussionmentioning
confidence: 51%
“…In the 'H spectrum the 5-and 6-hydrogen signals both appear as double doublets, coupled to each other, and separately to the 4-proton, as found in other related photoproducts containing the dihydronaphthalene skeleton (6)(7)(8). Of the hydrogens in the 11-and 12-methylene groups, one proton signal lies at a lower field than any of the others, and is assigned to the 12-exo hydrogen as it is in the deshielding zone of the fused benzene ring.…”
Section: Photochemical Rearrangementsmentioning
confidence: 59%
“…90% yeild. Refluxing of the adduct (2) with potassium tert-butoxide in tert-butanol (the conditions used by McCullough et al) afforded 2-carbamoy1-1,2-dihydrocyclobuta[a]naphthalene (4) in ca. 20% yield.…”
Section: Synthesis Of 2-cyano-12-dihydrocyclobuta[a]naphthalene and mentioning
confidence: 99%
“…Hence, we first re-examined the base-catalyzed elimination of methanol from the adduct (2). As a result, it was found that use of dry benzene instead of tert-butanol as a solvent, and a reduction in the reaction time, resulted in a satisfactory result.…”
Section: Synthesis Of 2-cyano-12-dihydrocyclobuta[a]naphthalene and mentioning
confidence: 99%